Law, Economics, and Beyond: A Case for Retheorizing the Business Corporation - Vasudev, P. (McGill Law Journal / Revue de droit de McGill)

(untitled) (McGill Law Journal / Revue de droit de McGill, 2010)
This essay presents a critical analysis of the economic theory of corporations and its idioms, such as “nexus of contracts”, “agency costs”, and “shareholder value”. It calls for the development of a richer and more inclusive theory of business corporations that draws on the experience of the last three decades and better addresses the needs of the post-Enron, post-AIG world.The author identifies the following shortcomings of the economic theory of corporations. First, the contractarian interpretation overlooks the role of law and public policy in corporations. Second, using share prices as the yardstick of corporate performance and encouraging practices such as the buyback of shares have serious implications for the competitiveness and sustainability of corporations. Third, there is inadequate attention to the characteristic and normative distinctions between debt and equity. And fourth, hostile takeovers are treated as virtually the only solution to entrenched managements. The problem of managerial power must be reviewed in the light of evidence regarding managerial power and the efficacy of boards. Equally, there is a case for developing a more deliberated, fair, and equitable policy on executive pay.